Microbiota-derived butyrate is an endogenous HIF prolyl hydroxylase inhibitor - Wang, Ruth X.; Henen, Morkos A.; Lee, J. Scott; Vögeli, Beat; Colgan, Sean P. (Gut microbes, 2021)
The gut microbiota is essential for human health. Microbial supply of short-chain fatty acids (SCFAs), particularly butyrate, is a well-established contributor to gut homeostasis and disease resistance. Reaching millimolar luminal concentrations, butyrate is sequestered and utilized in the colon as the favored energy source for intestinal epithelia. Given the steep oxygen gradient across the anoxic lumen and the highly oxygenated lamina propria, the colon provides a particularly interesting environment to study oxygen sensing. Previous studies have shown that the transcription factor hypoxia-inducible factor (HIF) is stabilized in healthy colonic epithelia. Here we show that butyrate directly inhibits HIF prolyl hydroxylases (PHDs) to stabilize HIF. We find that butyrate stabilizes HIF in vitro despite eliminating β-oxidation and resultant oxygen consumption. Using recombinant PHD protein in combination with nuclear magnetic resonance and enzymatic biochemical assays, we identify butyrate to bind and function as a unique, noncompetitive inhibitor of PHDs relative to other SCFAs. Butyrate inhibited PHD with a noncompetitive K i of 5.3 ± 0.5 mM, a physiologically relevant concentration. We also confirm that microbiota-derived butyrate is necessary to stabilize HIF in mice colonic tissue through antibiotic-induced butyrate depletion and reconstitution experiments. Our results suggest that the co-evolution of mammals and mutualistic microbiota has selected for butyrate to impact a critical gene regulation pathway that can be extended beyond the mammalian gut. As PHDs are a major target for drug development in the stabilization of HIF, butyrate holds great potential as a well-tolerated endogenous inhibitor with far-reaching therapeutic impact.